Early application of airway pressure release ventilation may reduce the duration of mechanical ventilation in acute respiratory distress syndrome - Zhou, Yongfang; Jin, Xiaodong; Lv, Yinxia; Wang, Peng; Yang, Yunqing; Liang, Guopeng; Wang, Bo; Kang, Yan (Intensive care medicine, 2017)
Purpose Experimental animal models of acute respiratory distress syndrome (ARDS) have shown that the updated airway pressure release ventilation (APRV) methodologies may significantly improve oxygenation, maximize lung recruitment, and attenuate lung injury, without circulatory depression. This led us to hypothesize that early application of APRV in patients with ARDS would allow pulmonary function to recover faster and would reduce the duration of mechanical ventilation as compared with low tidal volume lung protective ventilation (LTV). Methods A total of 138 patients with ARDS who received mechanical ventilation for <48 h between May 2015 to October 2016 while in the critical care medicine unit (ICU) of the West China Hospital of Sichuan University were enrolled in the study. Patients were randomly assigned to receive APRV ( n = 71) or LTV ( n = 67). The settings for APRV were: high airway pressure (P high ) set at the last plateau airway pressure (P plat ), not to exceed 30 cmH 2 O) and low airway pressure ( P low ) set at 5 cmH 2 O; the release phase (T low ) setting adjusted to terminate the peak expiratory flow rate to ≥ 50%; release frequency of 10–14 cycles/min. The settings for LTV were: target tidal volume of 6 mL/kg of predicted body weight; P plat not exceeding 30 cmH 2 O; positive end-expiratory pressure (PEEP) guided by the PEEP–FiO 2 table according to the ARDSnet protocol. The primary outcome was the number of days without mechanical ventilation from enrollment to day 28. The secondary endpoints included oxygenation, P plat , respiratory system compliance, and patient outcomes. Results Compared with the LTV group, patients in the APRV group had a higher median number of ventilator-free days {19 [interquartile range (IQR) 8–22] vs. 2 (IQR 0–15); P < 0.001}. This finding was independent of the coexisting differences in chronic disease. The APRV group had a shorter stay in the ICU ( P = 0.003). The ICU mortality rate was 19.7% in the APRV group versus 34.3% in the LTV group ( P = 0.053) and was associated with better oxygenation and respiratory system compliance, lower P plat , and less sedation requirement during the first week following enrollment ( P < 0.05, repeated-measures analysis of variance). Conclusions Compared with LTV, early application of APRV in patients with ARDS improved oxygenation and respiratory system compliance, decreased P plat and reduced the duration of both mechanical ventilation and ICU stay.